THE INFLUENCE OF ADVERTISING STAR CHARACTERISTICS ON MARKET SHARE: Beautiful and Famous Celebrity Endorser - Lestari, Fina Ayu (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Various ways are used to influence consumers to make purchases, one of which is by using advertising stars that are relevant to the product and target market. In the beauty business, using ad stars who are beautiful and popular is believed to have a broad influence on market share, so that product sales increase. This research was conducted to test the attractiveness of advertising stars on consumer purchasing decisions for a beauty product. To prove this conjecture, a quantitative approach is used with Particle Least Square analysis. Respondents in this study were users of Pixy brand beauty products in Gresik, East Java. Data collection was carried out purposively with a total of 100 respondents. The results of the study explained that more than 50% of consumers buy beauty products because they are influenced by advertisement stars, especially if the advertisement stars are their idols. So that the belief arises as followers to also be able to look beautiful like their idols. This was confirmed in a statistical test, in which the consumer's decision to buy Pixy brand beauty products in the city of Gresik was influenced by the attractiveness of advertising stars, which engendered trust.